Peran Media Sosial Dalam Meningkatkan Daya Saing Coffe Shop : Studi Kasus Digital Marketing Kopi Kenangan - Batubara, Rizki Wulanita; Yusuf, Aisyka Anindy (Digital Business Progress, 2025)
This article examines the role of social media in increasing the competitiveness of coffee shops in Indonesia, with a case study on Kopi Kenangan. The study shows that Kopi Kenangan has successfully utilized social media platforms such as Instagram and TikTok through interesting visual content, current trends, collaboration with influencers, and digital promotions integrated with applications. This strategy is able to build emotional closeness with customers, increase engagement and loyalty levels, and expand market reach. The use of social media as an innovative communication and promotion tool has proven effective in facing competition in the increasingly competitive coffee industry. The results of this study confirm that the success of modern businesses is highly dependent on creative and adaptive digital marketing strategies.